Alcoholic Hepatitis: Risk Factors, Pathogenesis, and Approach to Treatment. (4th February 2016) - Yeluru, Apurva; Cuthbert, Jennifer A.; Casey, Lisa; Mitchell, Mack C.
Abstract : Background: Alcoholic hepatitis (AH) is an inflammatory disorder of the liver characterized clinically by jaundice, hepatomegaly, and abdominal pain, and histologically by macrovesicular steatosis and necroinflammation. Methods: This clinical review will cover what is known about the pathogenesis, clinical presentation, current treatments, and novel therapies for AH. Results: The pathogenesis and treatment of AH remain areas of active research. Although abstinence is the cornerstone of therapy for all stages of alcoholic liver disease, corticosteroids have shown modest short‐term benefits in treatment of severe AH. Conclusions: Improved understanding of the pathogenesis of AH has expanded the range of potential treatments for this devastating disease. Several novel therapies are also currently in various stages of testing through clinical trials. Abstract : An integrated approach to treating alcoholic hepatitis: alcoholic hepatitis is an inflammatory disease of the liver that likely results from activation of Toll‐like receptors by LPS and pathogen‐associated molecular patterns (PAMPs) from a leaky/damaged gut mucosa leading to release of pro‐inflammatory cytokines including TNF‐ α, IL‐1‐ β, activation of inflammasomes and cell death via the caspase pathway. Each of these pathways of injury potentially provide a target for treatment, either individually or in combination.